Peran Artificial Intelligence dalam Mengembangkan Lingkungan Pembelajaran Berbasis Permainan yang Imersif (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
This study aims to examine the role of Artificial Intelligence (AI) in developing immersive game-based learning environments and its impact on educational technology. The method employed is a Systematic Literature Review, utilizing sources from Google Scholar, DOAJ, and Scopus for publications between 2014 and 2024. The findings indicate that the application of AI creates a more personalized, adaptive, and interactive learning environment. Techniques such as reinforcement learning enable characters in the games to function dynamically and respond to students' decisions, providing an engaging learning experience. Generative AI supports natural interactions with non-player characters (NPCs), particularly on platforms such as Roblox. Furthermore, AI's ability to monitor student data in real-time allows for rapid feedback and personalized content, proving to be more effective than traditional learning environments. AI-based learning environments enhance student engagement, motivation, and cognitive development by tailoring learning experiences to individual progress. Elements of gamification and immersive narratives also boost motivation, as well as critical thinking and problem-solving skills. AI-based virtual laboratories and immersive technologies such as VR and AR help bridge the gap between theory and practice, especially in STEM fields